RESILIENT INFRASTRUCTURE: IMPACTS OF ROADS ON POPULATION AND ECONOMIC GROWTH IN KADUNA METROPOLIS, KADUNA STATE, NIGERIA - Muhammed, Abdulkadir Yahaya; Sulaiman, Salamatu; Bello, Samira; Abdulkadir, Hindatu; Baba, Saadatu Umaru (FUDMA Journal of Sciences, 2023)
Road infrastructure is one of the critical infrastructure because it shapes the spatial structure of socio-economic activities and the well-being of the people. This study aims to bring out the correlation of the impact of road infrastructure on population and economic growth in Kaduna metropolis. A qualitative method using a thematic approach was used to collect data and analyze them. 46 participants were interviewed. From the analysis or results, two schools of thought emerged in connection with road infrastructure and population and economic growth. The first school of thought opines that road infrastructure is directly correlated with positive population and economic growth. This group is dominated by government agencies and transport functionaries. The second school of thought dominated by traders and consumers of goods did not see  correlation between road infrastructure and economic growth owing to the displacement of small businesses by the roadside and the increase journey to get or purchase goods.  However, irrespective of individual and/or collective views, the government of Kaduna State is trying to meet up with the sustainable development goals eight, nine and eleven which are directly connected  to decent work and economic growth; industry, innovation and infrastructure and sustainable cities and communities respectively. Thus, more findings reveal many roads either rehabilitated or constructed including underpass and overpass bridges across the metropolis including a four- hectare big shopping mall. It is recommended that government should be cautious when implementing this noble idea so that less injury is/will be inflicted on small-scale business owners and consumers.
Keywords: Economic growth; Kaduna metropolis; population; road infrastructure